The effect of phosphorus nutrition on the response of white clover (Trifolium repens L.) to elevated PCO2 - Almeida, J.P.F. (1998)
The first results from the suiss FACE experiment showed a sink-limitation in the response of Lolium perene to elevated PCO2.